Advances In Sustainable Materials And Green Construction Technologies: A Review - Putri Wiji Rahayu Rahayu; Adamu Abubakar Muhammad (International Journal of Sustainable Engineering Innovations, 2026)
Background of Study: Climate change, driven by human-induced greenhouse gas emissions, presents a global crisis. The construction sector is a primary contributor, responsible for 30–40% of global energy use and over 30% of emissions throughout the building life cycle. Despite innovations like low-carbon materials and Building Information Modeling (BIM), current research remains fragmented. A significant gap exists in integrating technical, economic, and environmental aspects into a single analytical framework. Aims Paper: This paper aims to identify trends in sustainable materials and green technologies through a systematic review. It evaluates their performance across technical, environmental, and economic dimensions while formulating future research directions to achieve sustainable development goals. Methods: A Systematic Literature Review (SLR) was conducted using the Scopus database (2016–2025). Five core keywords were used to identify relevant studies, which were then cleaned using OpenRefine and visualized via VOSviewer. Elicit AI assisted in screening and synthesizing the final 12 journal articles. Result: Analysis of 12 articles shows that experimental studies (50%) and Multi-Criteria Decision-Making (25%) are the dominant methodologies. Research primarily focuses on optimizing specific materials like waste-based concrete and geopolymers. While material innovation is a priority, there is limited integration of technical data with long-term Life Cycle Assessment (LCA) or life-cycle cost analysis. Cocnlusion: Current sustainable construction research emphasizes technical material optimization through experimental approaches. While decision-support models are evolving, empirical integration of the circular economy and LCA remains limited. Future research must adopt holistic frameworks, expand data sources, and include diverse geographical case studies to support effective sustainability practices.